Investment Management and Financial Intermediation Efficiency of Deposit Taking Saccos's in Kenya - Muriithi, Perminus Kariuki; Nasieku, Tabitha Nasieku; Memba, Florence Memba (International Journal of Finance, 2022)
Purpose: The purpose of the study will be to examine the influence of investment management on financial intermediation efficiency of deposit taking Savings and Credit Cooperative Societies in Kenya. Methodology: This study adopted a descriptive survey research design. Target population of the study was 174 DT SACCOs which were in operations as December 2020. Census approach was used to select 174 DT SACCOs. The study relied on secondary data that was collected from annual financial statement of DT SACCOs. Data was analyzed using descriptive statistics (mean, standard deviation) and inferential statistics; regression analysis to examine the nature of the influence of investment management on financial intermediation efficiency. Results: Results indicate that 57.38% of changes in financial intermediation efficiency of DT SACCOs was contributed by investment requirements. Further, there was a positive and significant influence of investment requirement on financial intermediation of DT SACCOs in Kenya (Î² = 0.071, p value < 0.05). The findings further revealed that financial performance as measured by profit before tax over total assets is positively related to Liquidity. Unique Contribution to Theory, Policy and Practices: There is need for management of DT SACCOs to enhance compliance with Investment managements policy guidelines and procedures. This would be achieved through management of working capital items such as management of cash balances. Dependent on investment policies in place DT SACCOs management may adopt investment models that would enable ease conversion of investment in non-tangible assets into cash.